Degradación del liderazgo sindical e indefensión gremialista de los trabajadores en el Ecuador periodo 2017-2019 - Llivichuzca Guartancela, Carmen Jazmín (My University, 2020)
The purpose of the research lies in the analysis of the degradation of union leadership and union defense of workers in Ecuador, focused on the development of strategies that are aimed at the formation and preparation of new union leaders with moral, ethical values and principles revolutionary Marxist ideologies, and in turn respecting the history and culture of those involved in the social, economic and political context. The general objective of the investigation is framed in identifying the causal factors that underlie the degradation of union leadership and the situation of union defenselessness in which workers are in Ecuador, based on the collection and analysis of theoretical correlation information to the problem of study, in perspective to the construction of an intervention proposal. The present research acquires theoretical foundations based on bibliographic references of generalized scientific articles in indexed journals, also acquires arguments to the epistemological referent in the rational-inductive paradigm obtained through the collection of bibliographic data.
El propósito de la investigación reside del análisis de la degradación de liderazgo sindical e indefensión gremialista de los trabajadores en el Ecuador, enfocado a la elaboración de estrategias que están dirigidas a la formación y preparación de nuevos líderes sindicales con valores morales, éticos y principios e ideologías marxistas revolucionarias, y a su vez respetando la historia y cultura de los involucrados en el contexto social, económico y político. El objetivo general de la investigación se enmarca en identificar los factores causales que subyacen en la degradación del liderazgo sindical y la situación de indefensión gremial en la que se encuentra los trabajadores en el Ecuador, a partir de la recopilación y análisis de información teórica en correlación al problema de estudio, en perspectiva a la construcción de una propuesta de intervención. La presente investigación adquiere fundamentos teóricos sustentados en referencias bibliográficas de artículos científicos generalizados en revistas indexadas, asimismo adquiere argumentos al referente epistemológico en el paradigma racional-deductivo obtenidos mediante la recopilación de datos bibliográficos.
Keywords: MOVIMIENTO; OBRERO; LIDER; SINDICALISMO